2017
DOI: 10.1371/journal.pntd.0005461
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the immune response by Fonsecaea pedrosoi morphotypes in the course of experimental chromoblastomycosis and their role on inflammatory response chronicity

Abstract: A common theme across multiple fungal pathogens is their ability to impair the establishment of a protective immune response. Although early inflammation is beneficial in containing the infection, an uncontrolled inflammatory response is detrimental and may eventually oppose disease eradication. Chromoblastomycosis (CBM), a cutaneous and subcutaneous mycosis, caused by dematiaceous fungi, is capable of inducing a chronic inflammatory response. Muriform cells, the parasitic form of Fonsecaea pedrosoi, are highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…To obtain purified conidia and hyphae, fungi propagules were grown in PDB supplemented with 100 mg/L −1 chloramphenicol, in a rotary shaker (120 rpm) at 30°C. Fungal purification was performed according to Siqueira et al ( 2017 ). Briefly, 15 days suspension containing conidia and hyphal fragments was subjected to successive filtrations through 70 μm and 40 μm cell strainers (BD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain purified conidia and hyphae, fungi propagules were grown in PDB supplemented with 100 mg/L −1 chloramphenicol, in a rotary shaker (120 rpm) at 30°C. Fungal purification was performed according to Siqueira et al ( 2017 ). Briefly, 15 days suspension containing conidia and hyphal fragments was subjected to successive filtrations through 70 μm and 40 μm cell strainers (BD).…”
Section: Methodsmentioning
confidence: 99%
“…Macrophage infection assays were adapted from Hayakawa et al ( 2006 ), Palmeira et al ( 2008 ) and Siqueira et al ( 2017 ). Mouse macrophages (J774 cell line) were plated in DMEM (Dulbecco's Modified Eagle's medium, Sigma) supplemented with 10% heat-inactivated fetal bovine serum (Gibco) and infected with conidia or hyphae of the Fonsecaea species at a multiplicity of infection (MOI) of 1.…”
Section: Methodsmentioning
confidence: 99%
“…It could change into muriform cells once infecting the host, especially in long‐standing lesions. Siqueira, I. M. et al found different F pedrosoi fungal forms trigger distinct infection patterns: hyphae and muriform cells were infective, with both morphotypes being able to establish murine CBM with skin lesions similar to that found in humans, whereas infection with conidia did not reach the chronic phase of the disease. Unfortunately, our induction of F monophora muriform cells in vitro was not satisfactory.…”
Section: Discussionmentioning
confidence: 81%
“…Since F. pedrosoi activates the NLRP3 inflammasome in vitro , we investigated whether in vivo activation occurs and the possible role of this process in controlling fungal infection. Employing a mouse model of subcutaneous F. pedrosoi infection ( 24 , 67 ), WT-infected mice showed a sustained production of IL-1β at all the time points analyzed, which was significantly reduced in mice lacking NLRP3. In addition, the NLRP3 inflammasome was also required for the production of IL-18, as assessed in the footpad macerate at 28 d.p.i.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans hyphae are better inducers and the only fungal form of A. fumigatus that activates the NLRP3 inflammasome ( 16 , 17 , 23 ). Indeed, we have recently showed that unlike conidia, the hyphae and muriform (sclerotic) cells of F. pedrosoi promote intense production of proinflammatory cytokines in vitro and in vivo ( 24 ). Among these cytokines, we observed IL-1β production, suggesting that F. pedrosoi could activate the inflammasome.…”
Section: Introductionmentioning
confidence: 99%